(untitled) (Journal of Technology and Operations Management, 2025)
Green manufacturing is a practice that aims to reduce waste and pollution throughout the manufacturing process. The research scope covers how the implementation of green manufacturing practices helps manufacturing companies to reduce GHG emissions. The main objective of the study is to determine the relationship between green manufacturing practices and GHG emissions and how knowledge, costs, regulations and technology moderate the relationship between green manufacturing practices and GHG emissions in Malaysia. This paper reviews the existing literature on the topic and proposes a conceptual framework of green manufacturing practices for Malaysian manufacturing industry context. This study intends to provide insights into green manufacturing and as well as to fill the research gaps in how green manufacturing helps in reducing GHG emissions.